Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan di Perusahaan Umum Daerah Gianyar - Satya Dinata, I Kadek Dipa (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the effect of work motivation and work discipline on the performance of employees of the Gianyar Regional Public Company. The research method used is quantitative. The location of the study in the Gianyar Regional Public Company The sample used was 36 respondents. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, Test t and Test F. Based on the results of the study, it was found that work motivation has a significant positive effect on employee performance, work discipline has a significant positive effect on employee performance, and simultaneously work motivation and work discipline have a positive and significant effect on employee performance. The suggestion in this study is that the Gianyar Regional Public Company should routinely provide training to employees, procure facilities that are lacking and replace facilities that are no longer suitable for use and provide reprimands or sanctions to employees who do not comply with all the rules set by the Company.